2012
DOI: 10.1590/s2236-89062012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos fisiológicos, anatômicos e ultra-estruturais do rizoma de Costus arabicus L. (Costaceae) sob condições de déficit hídrico

Abstract: -(Physiological, anatomical and ultrastructural aspects of the rhizome of Costus arabicus L. (Costaceae) under water defi cit conditions). Costus arabicus L. is an herbaceous species, native to the forest that accumulates starch in the rhizome as the main reserve carbohydrate. Water stress is one the most important environmental factor that regulates plant growth and development, leading to changes in physiological, biochemical and anatomical traits. The aim of this study was to evaluate the effect of water de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Cellular collapse of covering tissue and outer cortical layers was also observed in rhizomes of Costus arabicus , a starch accumulating species, under water deficit. The degree of tissue damage was dependent on the intensity and duration of the water deficit (Costa et al, 2012 ). Additionally, Zhang et al ( 2010 ) reported that water deficit could affect size distribution of starch granules in wheat cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular collapse of covering tissue and outer cortical layers was also observed in rhizomes of Costus arabicus , a starch accumulating species, under water deficit. The degree of tissue damage was dependent on the intensity and duration of the water deficit (Costa et al, 2012 ). Additionally, Zhang et al ( 2010 ) reported that water deficit could affect size distribution of starch granules in wheat cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, environmental factor such as soil conditions, water, light, temperature, etc., influence the morphophysiological characteristics of the plants and so, environmental changes can cause structural changes (Costa et al 2012;Alameda & Villar 2012;Aref et al 2013;Cambi et al 2016) and physiological (Warren et al 2011;Alameda & Villar 2012;Lu et al 2012;Cambi et al 2016;Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%